Relevansi dan Aktualisasi: Penerapan Hukum Acara Dalam Penyelesaian Talak Raj’i di Indonesia - Winda Fitri; Rini Rini; Vanessa Angel; Erika Emilia Putri (Pusat Riset dan Inovasi Nasional, 2023)
Raj'I divorces is one of the applicable divorces in Indonesia, regulated in the Compilation of Islamic Law Article 117 and Law Number 1 1974 concerning Marriage which is outlined in the divorce. This article will discuss the relevance of the religious court regulation as a form of actualization of the settlement of Raj'I divorce which can be caused by many things, such as infidelity as happened based on decision Number 2143/Pdt.G/2022/PA.Btm located in Batam, Riau Islands, Indonesia, due to the betrayal of the husband, so they decided to divorce. This research also uses a qualitative approach and secondary data. The result of the research conducted is that the procedural law has clearly regulated and relevant to the regulation of raj'I divorces in Indonesia. This refers to the arrangement of raj'I divorces which is not only regulated through national law but also through Islamic law which has been in line with social, cultural and traditions in the community. The existence of raj'i divorce is only one of several types of divorce regulated through Islamic law and can be integrated with the Muslim community in Indonesia.